Relação entre a biometria ultra-sonográfica em modo B do bulbo ocular e os diâmetros fronto occiptal e bizigomático em Canis familiaris - CARVALHO, Poliana Silva Beserra (2016)
In the experiment 31 healthy mongrel dogs, 8 months to 7 years of age, were used, 10 males and 21 females, weighing 1.5-28 kg. Initially, fronto-occipetal (FOD) and bizigomatic (BZD) diameters were measured using a caliper. The ophthalmologic transpalpebral B-mode ultrasonography (US) was performed to measure the ocular bulbi structures, as follows: The cornea thickness (D1), distance between cornea and anterior lens capsule (D2), distance between cornea and posterior lens capsule (D3), lens thickness (D4), lens diameter (D5), lens area (D6), distance between posterior lens capsule and retina (D7), distance between anterior lens capsule and retina (D8), and the distance between cornea and retina (D9). Except for D4, there were effect of FOD and BZD on the measures of the internal structures of BO. The Lineal Regression Analysis between the measures of the internal oculars structures and DFO and DBZ were significant for D1, D2, D3, D4, D5, D6, D7, D8 and D9.